Application of the Law on the Eradication of Corruption in Banking Crime Cases (Study of Several Judges' Decisions): Andrey Anandia Prahidayat, Waluyadi, Ari Nurhaqi (Focus Journal : Law Review, 2026)
This research aims to determine the basis for judges' considerations in rulings on banking cases that are corruption crimes, and to analyze the types of banking crimes that can be categorized as corruption. This research uses a normative juridical method with a statutory and case-based approach. The results show that judges' considerations in banking crime cases and corruption cases in the banking sector have fundamental differences. In banking crime cases, judges emphasize violations of banking regulations, the principle of prudence, and official responsibilities, without directly linking them to state finances. Meanwhile, in corruption cases, judges assess abuse of official authority, unlawful acts in the management of funds, and a direct link to state financial losses. The form of banking crime that can be categorized as corruption is determined by fulfilling the elements of abuse of authority, unlawful acts, and state financial losses. Therefore, this qualification is not automatic but must be based on a comprehensive legal assessment of the act, the perpetrator, and the resulting consequences.